Fenomena kepatuhan pajak sistem self assessment selama pandemi COVID-19 di UPPPD Kecamatan Taman Sari - Abrori, Mochamad Ali; Utaminingtyas, Tri Hesti; Zakaria, Adam (LPMP Imperium, 2023)
The implementation of Large-Scale Social Restrictions as known as PSBB by the Central Government and the Provincial Government of DKI Jakarta during the Covid-19 Pandemic finally brought a very bad risk, especially the entertainment industry in Jakarta. This study aims to find out how the attitude of the tax authorities in collecting entertainment taxes during the Covid-19 pandemic. The location of the research was carried out at the Regional Tax Collection Service Unit, Taman Sari District. This research is a qualitative research using a phenomenological approach. The phenomenological approach was chosen to find out the experience and point of view of the tax authorities in dealing with the entertainment industry organizers. The results show that the persuasive approach is one of the alternative efforts in maximizing tax revenue with a self-assessment system such as the entertainment tax during the Covid-19 pandemic. In addition, tax policies in the form of stimulus such as relaxation of payments and reduction of tax sanctions are also needed so that taxpayers are willing to pay taxes due and tax arrears.